PENGARUH STAKEHOLDER PRESSURE DAN KINERJA KEUANGAN PERUSAHAAN TERHADAP SUSTAINABILITY REPORT QUALITY - Silvana, Silvana; Khomsyiah, Khomsyiah (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2023)
In recent years, there has been an important issue regarding environmental damage and pollution that has occurred in Indonesia, this has finally triggered corporate awareness of the importance of disclosing social responsibility. Therefore, this study aims to examine the effect of stakeholder pressure and company financial performance on sustainability report quality. The sample in this study were 48 companies listed on the LQ 45 Index in 2018-2021. The sample of this research was determined by purposive sampling method. The type of data used is secondary data. The analytical method used is multiple regression analysis. The results of this study indicate that there is a positive influence on environmentally sensitive industries and company performance on sustainability report quality, while industries close to consumers, employee-oriented industries, and investor-oriented industries do not have an influence on sustainability report quality. It can be concluded that the more sensitive a company is to the environment and is included in a high profile industry, it will get higher pressure from the environment to disclose its activities. Likewise with financial performance (ROA and DER), the higher the company's financial performance, the more it will affect the sustainability report quality.